Structure-Based Virtual Screening and Molecular Docking of Dual Inhibitors of Plasmodium Falciparum Prolyl-tRNA Synthetase - Achsendo Yuniarta, Tegar; Arief, Imtiyaz Izdihar; Syabihah, Haura; Fakih, Taufik Muhammad (Farmasains : Jurnal Farmasi dan Ilmu Kesehatan, 2026)
Malaria is a disease caused by Plasmodium parasites, which remains a global problem including in Indonesia. One of the main types of parasites that cause malaria is Plasmodium falciparum which currently shows a tendency to be resistant to artemisinin-based combination therapy (ACT). This highlights the need to discover of more effective new drugs. This study aims to discover new drug candidates capable of overcoming ACT resistance using a computational approach. The methods used include structure-based pharmacophore modeling using the Pharmit webserver, virtual screening using the ChemDiv database, molecule docking using AutoDock Vina, and evaluation of ADME parameters using the SwissADME webserver. The molecular target used was the prolyl-tRNA synthetase enzyme (PDB ID: 4YDQ) with halofuginone as the reference compound. The pharmacophore screening successfully identified 312 hit compounds. Molecular docking using AutoDock Vina showed that 164 compounds had better binding affinity than halofuginone. Evaluation of ADME parameters showed that 11 compounds met the pharmacokinetic and toxicity criteria. Among them, ChemDiv-1481-0030 compound showed a binding affinity value of -10.6 kcal/mol with an 80% similarity in residue interactions compared to halofuginone. These results show that ChemDiv-1481-0030 has potential as an antimalarial drug candidate that works through the mechanism of inhibiting the PfPRS enzyme.